Analysis of the Vibration Characteristic for Heavy Duty Gear Under Different Load Levels - Guan Xiaoyang; Long Zhenhai (Jixie chuandong, 2017)
The vibration acceleration signals of two gearboxes under the load condition of 1 600 3 000 N·m are collected.The changes of time domain characteristic parameters and the sensitivity of gear meshing frequency and harmonics amplitude to the load change are analyzed.The results show that the gear meshing frequency amplitude is approximately linear with the load level.Both of the harmonic frequency 3fmof gearbox A,the harmonic frequency 3fm,4fmand high order harmonic frequency 10fm 13 fmof gearbox B are sensitive to the load level.The results have some significance for the further study of vibration characteristic on heavy duty gear transmission.